2010
DOI: 10.1007/s10722-010-9578-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of genetic variability of Solanum habrochaites in its natural area of distribution

Abstract: The tomato wild relative species Solanum habrochaites (previously known as Lycopersicon hirsutum) is a potential source of novel genes for tomato breeding. It shows resistance to many diseases and pests, cold tolerance and fruit quality traits. This species inhabits the western Andean slopes at high elevations from central Ecuador to central Peru. In this study the genetic variation of S. habrochaites was studied using 91 accessions from the whole range of distribution of this species. To this end, we employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 34 publications
(44 reference statements)
2
32
0
2
Order By: Relevance
“…This is indicated by the high similarity coefficient of the 29 cultivated tomatoes (0.845) in this study. By contrast, wild tomatoes, with a lot of valuable genes, are important resources for improving the tolerance to both biotic and abiotic stress, such as S. habrochaites (Hanson et al, 2007;Sifres et al, 2011), which could expand the genetic base of cultivated tomatoes. The 14 wild tomatoes that were included in this study enriched the genetic diversity as indicated by i) their scattered distribution in the three-dimensional PCA plot ( Figure 1); ii) the large genetic distance between them and the cultivated tomatoes ( Figure 3); and iii) the lower similarity coefficient of the wild tomatoes (0.627) as compared to the similarity coefficient of the cultivated tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…This is indicated by the high similarity coefficient of the 29 cultivated tomatoes (0.845) in this study. By contrast, wild tomatoes, with a lot of valuable genes, are important resources for improving the tolerance to both biotic and abiotic stress, such as S. habrochaites (Hanson et al, 2007;Sifres et al, 2011), which could expand the genetic base of cultivated tomatoes. The 14 wild tomatoes that were included in this study enriched the genetic diversity as indicated by i) their scattered distribution in the three-dimensional PCA plot ( Figure 1); ii) the large genetic distance between them and the cultivated tomatoes ( Figure 3); and iii) the lower similarity coefficient of the wild tomatoes (0.627) as compared to the similarity coefficient of the cultivated tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an interest in the possible antimicrobial or insecticidal roles of these metabolites, relatively little is known about their structural diversity or biosynthesis (Ghangas and Steffens, 1993). To document acylsugar diversity within a single species, we analyzed 80 S. habrochaites accessions collected from throughout the range of the species (Supplemental Table S1; Sifres et al, 2011) and M82 cultivated tomato (S. lycopersicum).…”
Section: Overview Of the Approachmentioning
confidence: 99%
“…The loss of SI at the northern range margin is correlated with the loss of pistil-side SI factor S-RNase [6, 31, 46]; whereas southern S. habrochaites SC populations express an S-RNase protein with little or no RNase activity [31]. The genetic structure of S. habrochaites is consistent with the spread of populations both north and south from a central origin, with central SI populations showing the highest levels of diversity [45, 47]. Interestingly, the types and strengths of reproductive barriers displayed by a number of populations also follow this same latitudinal axis of divergence [6, 45].…”
Section: Introductionmentioning
confidence: 99%